SPATIAL PLANNING AND HOUSING REGULATIONS FOR COSMO PARK THAMRIN CITY, CENTRAL JAKARTA - Helima Hutagaol; Akhmad Faruq; Irvon Dasrah; Rachmaiyanti Rachmaiyanti (Universitas Dharmawangsa Medan, 2025)
The development of the Jakarta metropolitan area encourages the emergence of mixed-use development concepts that integrate residential functions with commercial activities in a single vertical complex. Cosmo Park Housing, located above Thamrin City Mall, represents an innovation in vertical space utilization, yet raises issues regarding spatial planning compliance and regulatory adherence. This research employs a normative juridical approach with library research methods to analyze the conformity of space utilization with zoning regulations, compliance with spatial planning regulations, and implications of mixed-use models on space utilization control in strategic areas. Research findings indicate discrepancies between initial Building Permits and construction realization, legal antinomy in determining ownership status, and regulatory void regarding technical integration of horizontal housing with vertical commercial structures. Regulatory gaps and licensing practices indicate weak supervision mechanisms and harmonization of legal instruments. This research recommends the formulation of specific regulations, strengthening institutional capacity, implementation of public participation, and harmonization of legislative regulations to ensure sustainable mixed-use development that complies with spatial planning principles.